2020
DOI: 10.3390/ijms21197187
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between P2X and NMDA Receptors

Abstract: Purinergic P2X receptors (P2X) are ATP-gated ion channels widely expressed in the CNS. While the direct contribution of P2X to synaptic transmission is uncertain, P2X reportedly affect N-methyl-D-aspartate receptor (NMDAR) activity, which has given rise to competing theories on the role of P2X in the modulation of synapses. However, P2X have also been shown to participate in receptor cross-talk: an interaction where one receptor (e.g., P2X2) directly influences the activity of another (e.g., nicotinic, 5-HT3 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
(89 reference statements)
0
7
0
1
Order By: Relevance
“…142 It is reported that both P2X2 and P2X4 interact with NMDARs in an inhibited manner. 143 Ca 2+ entry through P2X2Rs or P2X4Rs…”
Section: Stress (Csds) Conditional Knockout Of P2x2 Receptors In Pyra...mentioning
confidence: 99%
“…142 It is reported that both P2X2 and P2X4 interact with NMDARs in an inhibited manner. 143 Ca 2+ entry through P2X2Rs or P2X4Rs…”
Section: Stress (Csds) Conditional Knockout Of P2x2 Receptors In Pyra...mentioning
confidence: 99%
“…In addition to the above regulation mechanisms, NMDAR is also modulated by other pathways. Related studies have demonstrated that both purinergic P2X receptors (P2X2) and P2X4 interact with NMDAR in an inhibitory manner (Rodriguez et al, 2020). Meanwhile, SULT4A1 promotes the formation of the PSD-95/NMDAR complex to modulate synaptic development and function (Culotta et al, 2020).…”
Section: Influence Of Related Proteins and Signaling Pathways On Nmdarmentioning
confidence: 99%
“…P2X receptors further modulate the activity of GABAa receptors ( Boué-Grabot et al, 2004 ; Toulmé et al, 2007 ; Jo et al, 2011 ), nACh receptors ( Khakh et al, 2000 ), and 5-hydroxytryptamine receptor 3A ( Boué-Grabot et al, 2003 ; Emerit et al, 2016 ; Soto et al, 2020 ). Coexpression of P2X receptors and NMDARs in oocytes showed that they interact via the C-terminal domain of NMDAR, and their activation inhibits NMDAR-dependent currents ( Rodriguez et al, 2020 ).…”
Section: The Nmdar Surface Cis-interactome: Current Viewmentioning
confidence: 99%